How police body-worn cameras can facilitate misidentification in domestic and family violence responses - Iliadis, Mary (Trends & issues in crime and criminal justice, 2024)
Police body-worn camera (BWC) technologies—affixed to a vest, sunglasses or cap—are deployed by all Australian police agencies, including in frontline responses to domestic and family violence (DFV). This paper presents the findings from the first Australian study focused on how women DFV victim-survivors view and experience BWCs in police call-outs and legal proceedings. Informed by a national survey of 119 victim-survivors, it explores two key concerns relating to the potential consequences of BWC footage: (1) it may facilitate misidentification of the primary aggressor, and (2) perpetrators may use the BWC to present (false) evidence of themselves as blameless.